2018
DOI: 10.1055/s-0037-1615297
|View full text |Cite
|
Sign up to set email alerts
|

Closed Suction Drainage after Primary Total Knee Arthroplasty: A Prospective Randomized Trial

Abstract: The discussion as to whether or not to use closed suction drainage (CSD) after total knee arthroplasty (TKA) is still ongoing. A multitude of surgical techniques makes comparison between studies difficult. The aim of the present study was to investigate the benefit of CSD versus nondrainage following primary TKA when operating after exsanguination (by means of a rubber Esmarch bandage) with a tourniquet and without any form of hemostasis. A prospective randomized trial was performed with a homogeneous sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…After abdominal surgery (laparotomy), Higson et al found a duplication of infection using non-aspirating drainage, whereas other studies did not confirm this association [25]. Drains can generally lead to a reduction in pain after surgeries such as total knee arthroplasty, but the results in this randomized prospective study were only confirmed in the early-term but not long-term follow-up [17]. However, in considering the postoperative pain in other disciplines, Schietroma et al found that routine drain placement after thyroidectomy is not necessary, and avoiding drainage was associated with less postoperative pain [44].…”
Section: Possible Complications and Side Effects After Placement Of Smentioning
confidence: 58%
“…After abdominal surgery (laparotomy), Higson et al found a duplication of infection using non-aspirating drainage, whereas other studies did not confirm this association [25]. Drains can generally lead to a reduction in pain after surgeries such as total knee arthroplasty, but the results in this randomized prospective study were only confirmed in the early-term but not long-term follow-up [17]. However, in considering the postoperative pain in other disciplines, Schietroma et al found that routine drain placement after thyroidectomy is not necessary, and avoiding drainage was associated with less postoperative pain [44].…”
Section: Possible Complications and Side Effects After Placement Of Smentioning
confidence: 58%
“…However, recent studies showed the otherwise. Multiple clinical trials indicated that CSD offered no additional benefits after TKA [3][4][5]. In addition, many CSD-related side effects, including retrograde infection, increased the loss of blood, and prolonged hospital stay time, were reported [6].…”
Section: Introductionmentioning
confidence: 99%
“…The posterior cruciate-stabilizing prostheses were fixed with bone cement, the surface of the patella was not replaced, only the patellar osteophytes were repaired, and the area around the patella was denervated with an electrotome. 5 All drugs were allocated with a sterile syringe in 20 mL increments by surgical personnel unassociated with this study, and the drugs were injected subcutaneously by the surgeon around the posterior knee, medial and lateral collateral ligaments, quadriceps tendon, patellar tendon, and incision edge before suturing. The trial group was administered 20 mL of magnesium sulfate 250 mg þ levobupivacaine 50 mg þ triamcinolone 25 mg þ 0.9% normal saline, and the control group was administered 20 mL of levobupivacaine 50 mg þ triamcinolone 25 mg þ 0.9% normal saline.…”
Section: Methodsmentioning
confidence: 99%